Skills and Knowledge Development Training for Students in the Tourism Industry at SMKN 1 Bintan Utara - Lubis, Arina Luthfini; Supardi; Fatimah, Zahara; Novianti, Jenni (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
This community service program aims to develop the practical skills and tourism knowledge of students at SMKN 1 Bintan Utara, given the rapid development of the tourism sector in Bintan which creates a need for skilled workers. Students need skills that are in line with hospitality industry standards, such as excellent service, front office management, and the use of digital technology. This training is designed to bridge the gap between classroom theory and the demands of the working world through various methods, such as lectures, simulations, and hands-on practice, which provide real learning experiences. In this training, students participate in scenarios that train them to face live situations in the world of work, helping them master essential skills in customer service and the use of digital technology in tourism. The results of this program show an increase in students' understanding and confidence in their skills. They also felt more prepared to enter the workforce after completing the training. With training that focuses on practical skills development, vocational schools such as SMKN 1 Bintan Utara can produce graduates who are ready to compete in the tourism labor market, both locally and internationally. The program emphasizes the importance of aligning vocational education with industry needs to support the development of the local tourism economy and improve workforce competitiveness.